Analysis of Teacher Problems Related to Learning Devices Using the Mikir Approach of SMP Students - Setijawati, Etik; Theodora Maasawet, Elsje; Hudiyono, Yusak (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2023)
In science subjects students must master knowledge well so that they are able to think critically to be able to solve problems related to the material, therefore learning tools are needed that can accommodate student activities so that learning objectives can be achieved. The aims of this research are: (1). To get an overview of the constraints experienced by teachers in preparing learning tools with the MIKiR approach (2). To get an overview of the extent of the teacher's constraints in recognizing and implementing active learning with the MIKiR approach in training students' critical thinking skills (3). To obtain an overview of the application of the type of assessment carried out by the teacher in measuring student learning outcomes and critical thinking skills. The data collection technique used observation with a survey method in the form of a questionnaire distributed to 6 schools in Muara Badak with 10 science teachers as respondents. Researchers obtained data from the recapitulation of answers to all respondents' questionnaires, namely 1) The teacher had difficulty compiling learning tools so that they had implications when using learning devices in teaching and learning activities. From the survey results, it was obtained that 80% of respondents had difficulty compiling learning tools and 50% had difficulty using them in learning. 2). The teacher only knows active learning with the MIKiR approach but does not implement it in learning because he does not know the implementation steps. Data obtained 100% of respondents already know the MIKiR approach, but only 30% of respondents implement the MIKiR approach and 67% experience problems in implementing it. 3) The teacher's lack of ability to assess critical thinking skills is caused by a lack of knowledge of critical thinking indicators. It was found that 80% of respondents knew a small proportion of critical thinking indicators but only 30% implemented these indicators. From the observation results, it was also obtained data that 100% of respondents felt the need and 80% of respondents were willing to implement the MIKiR approach in their schools. The need for assistance in the preparation of tools and modeling the MIKiR approach in training students to think critically in the hope that an increase in science learning outcomes will be obtained.